Xạ trị đích trong mổ với hệ thống Intrabeam: kỹ thuật mới trong điều trị ung thư vú tại Việt Nam - Tùng, Nguyễn Đình; Hiệp, Phạm Như; Dũng, Nguyễn Việt; Phúc, Nguyễn Văn; Thành, Trần Văn; Tuấn, Nguyễn Hữu Minh; Dũng, Nguyễn Cao (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
AA